Gaya Guru dalam Proses Pembelajaran SKI di MTS Al-Jam’iyatul Washliyah Tembung - Hasmar Husain Rangkuti; Mahariah Mahariah; Enni Nazrah Pulungan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the teacher's style in the SKI learning process at MTs Al-Jam'iyatul Washliyah Tembung and its impact on learning effectiveness. The main focus of this study is to understand how the teaching style used by teachers affects students' participation and understanding in SKI lessons.This study uses a qualitative research method using observation methods, in-depth interviews and documentation studies. The subjects of the study consisted of SKI teachers at MTs Al-Jam’iyatul Washliyah Tembung and students who participated in the SKI learning process. The results of this study indicate that the teaching styles of SKI teachers can be categorized into three main approaches, namely instructional, motivational, and adaptive. The instructional approach emphasizes providing clear techniques and strategies to ensure that students understand the material well. The motivational approach aims to encourage students' enthusiasm for learning, increase their involvement during learning, and inspire self-confidence. Meanwhile, the adaptive approach is used to adjust teaching methods to the needs and characteristics of each individual.